STUDI KELAYAKAN BISNIS PADA PERENCANAAN USAHA CAFÉ KULINER DI KOTA SURABAYA - Heri T. Prasetia (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2014)
Feasibility study is the tool that is able to be consideration materials in making the decisions to receive or reject the investment proposed in developing or establishing the project/business planning. The research about analysis of business feasibility, instead of to know whether it is feasible or not of the value of investment criteria, it is also to know the amount of investment funds that needed, the existing market share, and any constraints that will be possible to occurs in the process of establishing that type of business. As for the objectives that will be obtained from this research is to conduct the analysis of business feasibility as viewed from several aspects, that are financial aspect, and social aspect.